2017
DOI: 10.1002/aur.1819
|View full text |Cite
|
Sign up to set email alerts
|

Empathic responding in preschool‐aged children with familial risk for autism

Abstract: Individuals with autism spectrum disorder (ASD) show deficits in social and emotional reciprocity, which often include empathic responding. The younger siblings of children with ASD (high-risk siblings) are at elevated risk for ASD and for subclinical deficits in social-emotional functioning. Higher levels of empathy in high-risk siblings during the second and third years of life predict fewer ASD symptoms and likelihood of diagnosis. We conducted a multi-method investigation of empathic responding to an exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Specifically, when an adult was in pain, autistic individuals usually showed less visible emotional arousal than their non-autistic peers (Butean et al, 2014; Campbell et al, 2017; McDonald & Messinger, 2012). The exception to this is a study by McDonald and colleagues (2017), where although the difference between groups was not significant, a trend in the same direction was present. When an experimenter expressed distress about losing his/ her watch however, autistic (pre-)adolescents showed as much visible emotional arousal as their non-autistic peers (Newbigin et al, 2016).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Specifically, when an adult was in pain, autistic individuals usually showed less visible emotional arousal than their non-autistic peers (Butean et al, 2014; Campbell et al, 2017; McDonald & Messinger, 2012). The exception to this is a study by McDonald and colleagues (2017), where although the difference between groups was not significant, a trend in the same direction was present. When an experimenter expressed distress about losing his/ her watch however, autistic (pre-)adolescents showed as much visible emotional arousal as their non-autistic peers (Newbigin et al, 2016).…”
Section: Introductionmentioning
confidence: 70%
“…Such studies provide us with an understanding of more real-life social responses in various contexts, when compared to the use of imaged or videos. Examples of stimuli include an adult hurting him/ herself or being in pain (Butean et al, 2014; Campbell et al, 2017; McDonald et al, 2017; McDonald & Messinger, 2012), receiving bad news (Scheeren et al, 2013), losing her watch/torn drawing (Newbigin et al, 2016), or a peer being excluded from an online ball game (Deschamps et al, 2014). By observing and scoring participant’s visible responses in the video recordings, these studies examine the level of attention to the event, the visible emotional arousal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because TSC is often diagnosed in utero [11,12], these infants can be monitored for signs of atypical development well before a clinical ASD diagnosis is made. In a previous longitudinal study of early development, we found that infants with TSC who developed ASD demonstrated marked social communication and nonverbal cognitive delays by age 12 months [13,14], with deficits in nonverbal communication skills such as eye contact, coordination of gaze, engagement, and social referencing. Despite these clear behavioral markers of atypical development in early infancy, most infants in this study were not receiving targeted social communication interventions, with therapeutic effort focused instead on global development (such as physical therapy to address delayed motor skills).…”
Section: Introductionmentioning
confidence: 81%
“…A study using a well-validated, behavioral measure of prosocial behavior revealed that autistic children exhibited similar levels of prosocial behavior to nonautistic children (Deschamps, Been, & Matthys, 2014). A study using another behavioral measure of prosocial behavior also revealed no differences in prosocial behavior between autistic and non-autistic children (McDonald, Murphy, & Messinger, 2017).…”
Section: Are Reduced Prosocial Behaviors An Aspect Of the Bap?mentioning
confidence: 92%